PEMIKIRAN KH.BASUNI AZAM DALAM MENGEMBANGKAN PENDIDIKAN KARAKTER DI PONDOK MODERN AL-RIFA’IE SATU, DESA KETAWANG GONDANGLEGI, MALANG - Ervina Rahma Dwi Andriyani; Anwar Sa’dullah; Jazari Jazari (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Kh. Basuni Azam is one of the Kyai in Ketawang village, Gondanglegi, district of Malang. Being the chairman of the foundation became his responsibility in developing character education in Pesantren. With the background of diverse students, both in terms of economic, social, cultural, language and the region makes every students have a different character. So what is the view KH. Basuni Azam in character education at Pondok Modern Al-Rifa'ie Satu, Ketawang village, Gondanglegi, Malang. How is the direction and strategy of character development, as well as the orientation of pesantren development. The study uses data collection methods with interviews and documentation. Character education is an education of Akhlaqul Karimah, which can be formed according to where the individual lives and not the innate birth. The development of character education leads to the character of caring, independent, Creative Tawadhu, Qanaah, honest, Amanah, with the strategy of routing activities, transparency, conditioning and organization. The orientation of development is to strengthen the integrity of education, the competence of students, institutional and facilities and infrastructure.